2016
DOI: 10.1093/gji/ggw459
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional resistivity structure of Asama Volcano revealed by data-space magnetotelluric inversion using unstructured tetrahedral elements

Abstract: S U M M A R YAsama Volcano is an andesitic composite volcano and one of the most active volcanoes in Japan. In order to reveal electrical resistivity structure beneath the volcano accurately, we performed a 3-D inversion of dense magnetotelluric survey data. In order to prevent misinterpretation of the subsurface resistivity due to the steep topography around Asama Volcano, we used an unstructured tetrahedral mesh to represent the topography. Furthermore, we reduced the calculation time by transforming the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Such a bell-shaped conductor beneath the central cone or geothermal/fumarolic area has been previously detected at other volcanoes (e.g. Nurhasan et al 2006;Kanda et al 2008;Komori et al 2013;Yamaya et al 2013;Usui et al 2017). With reference to the conceptual model of a geothermal system described by Pellerin et al (1996), we interpret that the bell-shaped conductor and the resistive body represent an impermeable layer consisting of altered clays and a bounded hydrothermal reservoir, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Such a bell-shaped conductor beneath the central cone or geothermal/fumarolic area has been previously detected at other volcanoes (e.g. Nurhasan et al 2006;Kanda et al 2008;Komori et al 2013;Yamaya et al 2013;Usui et al 2017). With reference to the conceptual model of a geothermal system described by Pellerin et al (1996), we interpret that the bell-shaped conductor and the resistive body represent an impermeable layer consisting of altered clays and a bounded hydrothermal reservoir, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Here, we used a fixed value of β 2 = 0.01 since several reports had demonstrated that such a small trade-off parameter was sufficient for the MT inversion (e.g. Sasaki and Meju 2006;Avdeeva et al 2015;Usui et al 2017). However, we ran six inversions with various values of α 2 (100, 31.6, 10, 3.16, 1.0 and 0.316) and determined the performance of each model in terms of both its fit to the various parts of the dataset and the differences with the other models.…”
Section: Three-dimensional Inversion and Modelled Resistivity Structurementioning
confidence: 99%
See 1 more Smart Citation
“…There are three measurement sites within the crater system, around which there is steep topography. Therefore, we performed 3-D inversion with a finite element code utilizing an unstructured tetrahedral mesh that can incorporate topography into a resistivity model (FEM-TIC; Usui 2015; Usui et al 2017). This code has been applied successfully to volcanic areas at Asama volcano (Usui et al 2017) and Hakone volcano (Yoshimura et al 2018).…”
Section: -D Inversionmentioning
confidence: 99%
“…Furthermore, in some other geoelectric and geomagnetic exploration methods, FEM using an unstructured tetrahedral mesh has been increasingly used for 3-D modelling owing to its capability of incorporating precise topography and bathymetry into a computational mesh with a practical number of elements (Günther et al 2006;Schwarzbach & Haber 2013;Usui 2015). For 3-D land MT problem, Usui (2015) demonstrated that the approximation error of topographic expression can be reduced sufficiently by using an unstructured tetrahedral mesh, and Usui et al (2017) estimated the 3-D resistivity structure of Asama Volcano with a data-space MT inversion code using mesh of that type. In addition, Schwarzbach & Haber (2013) demonstrated the applicability of an unstructured tetrahedral mesh to 3-D marine controlled source electromagnetics.…”
mentioning
confidence: 99%